ANTIOXIDANT EFFECT OF Buchholzia coriacea ETHANOL LEAF-EXTRACT AND FRACTIONS ON FREUND’S ADJUVANT-INDUCED ARTHRITIS IN ALBINO RATS: A COMPARATIVE STUDY - Esther Ugo Alum (Slovenian Veterinary Research, 2022)
Abstract: Several studies have implicated reactive oxygen species in perpetuation of inflammation and subsequent destruction of joints in patients with arthritis. Antioxidant effects of Buchholzia coriacea ethanol leaf-extract, aqueous and ethyl acetate fractions on oxidative stress indices in rheumatoid arthritic female wistar albino rats were examined. 180 rats were randomly divided into 12 groups. Fifteen rats were placed in each group. Rats without arthritis were placed in Group 1. Rheumatoid arthritis was induced in groups 2 to 12 by intradermal injection of 0.1 ml complete Freund’s adjuvant into the left hind paws of rats. Group 2 (arthritic rats) did not receive any treatment but rather were given normal saline while group 3 (arthritic rats) received 5 mg/kg indomethacinTM (a standard drug). Rats in Groups 4 to 12 were administered the samples at doses of 200, 400 and 800 mg/kg body weight. Freund’s adjuvant administration led to inflammation and oxidative stress which were marked by significant (P<0.05) increase in paw sizes, oxidative stress markers and reduced body weight of the rats. Arthritic rats were treated with standard drug and samples (at varied doses) and this resulted to reversal of the trend of those parameters in a time and dose-dependent manner. Rats that received 800 mg/kg of the aqueous fraction displayed the best desirable result which was similar to the effect of indomethacin. Thus, Buchholzia coriacea ethanol extract and fractions may be useful in the management of oxidative stress which is very common among individuals with rheumatoid arthritis.